Williams gynecology - Hoffman, Barbara L. (New York : McGraw-Hill, 2020)
"The only gynecological text to combine a medical reference and surgical procedural atlas in one beautifully illustrated volume - now updated and revised in a fourth edition"--
Includes bibliographical references and index.
Catalography
Description based on print version record; resource not viewed.
Keywords: Gynecology